ANALYSIS THAT INFLUENCES THE PERFORMANCE OF HOME INDUSTRIAL EMPLOYEES IN DURUNGBEDUG VILLAGE, SIDOARJO DISTRICT, SIDOARJO DISTRICT - Indira Shofia Maulida; Ike Susanti; Ruswaji Ruswaji; Bella Fernanda (Jurnal Ekonomi, 2023)
Soybean became known in Indonesia since the 16th century. Initially, the spread and cultivation of soybeans was on the island of Java, then developed to Bali, Nusa Tenggara and other islands. Soybean is one of the main ingredients in the process of making tofu. Industry can run well because it is influenced by employee performance. The purpose of this research is to analyze the performance of employees in the tofu industry in Durungbedug Village, Sidoarjo District, Sidoarjo Regency. The method used in this research is Descriptive – Quantitative. Using a sample of tofu industry employees, the analytical tool used is multiple linear regression, to test the hypothesis used the coefficient of determination, F test and T test. The results of data processing, namely the T-test, obtained t count for work discipline of 1.592, motivation of 0.856 and leadership style 2.815. To determine the t table, use the statistical attachment t table, using α = 5%. The procedure for testing the t test is to use a 2-tailed test (a = 5% : 2 = 2.5%), with (df) n-1 or 50-1=49. Then obtained t table 2.009. The results of the multiple linear regression test ???? = 1.608 + ????.328???????? + ????.410???????? + ????.554???????? + ???? namely the leadership style variable (X3) is more dominant in influencing the variable (Y) namely employee performance, this is evidenced by the value of the regression coefficient of 0.554 . Which is greater than the regression coefficient variable work discipline (X1) and motivation (X3). The results of the F-test show that work discipline (X1), motivation (X2), and leadership style (X3) simultaneously affect employee performance (Y). Where is the calculated F count of 24.362 with a significance level of 0.05.